A case study on botanical pesticides and vermicompost fertilizer for adopting new agricultural practice by farmers - Kaphle, Manoj; Bastakoti, Nagendra (Journal of Agriculture and Environment, 2018)
For last 3 years, vegetable growers from Devdaha and Kerawani VDC of Rupandehi and Daunnedevi and Rupaulia VDC of Nawalparasi districts Nepal are concerned to minimize the practices of using chemical pesticides exploring several options. Action research was carried out to dessiminate the effect of botanical pesticide and vermi-compost fertilizer with major aspects: perception and adaptation. Household surveys and focus group discussions (FGDs) were carried out which was analyzed measuring frequency; percentage; indexing; mean and standard deviation. Results show that the adoption rate of botanical-pesticides and vermicompost was increased by 45% and 60% respectively. More than 80% farmers were motivated towards the use of vermi-compost and botanical pesticides. Vermi-compost was also found cost efficient comparing with Urea. More could have been done in transforming conventional farming into an organic one in studied area, where commercial olericulture has been seen as a booming business.